Effect of an Ultra-Endurance Event on Cardiovascular Function and Cognitive Performance in Marathon Runners - Perrotta, Andrew S.; Jeklin, Andrew T.; Bredin, Shannon S. D.; Shellington, Erin M.; Kaufman, Kai L.; de Faye, Amanda; Miles, Rosalin M.; Warburton, Darren E. R. (Frontiers in Physiology, 2022)
Background: Ultra-marathon running participation has become increasingly more popular in recent years, however there is inconclusive evidence concerning the effects of participation on cognition and cardiovascular function. The purpose of this paper was to examine alterations in cardiovascular function and cognitive performance and their association in marathon runners prior to and following an ultra-endurance event. Methods: 24 runners (19 males & 5 females) participated in an ultra-marathon race (FatDog120) held in British Columbia, Canada. Participants competed in varying races distances (48 km (n = 2), 80 km (n = 7), 113 km (n = 3), and 193 km (n = 12)). Cognition was assessed prior to and upon race completion using simple reaction time, choice reaction time, discrimination reaction time, and recognition memory (% correct). Cardiovascular function was assessed prior to and upon race completion using radial applanation tonometry for diastolic pulse contour examination. Results: Cognitive performance displayed significantly (p < 0.05) slower reaction times for simple (30.2%, p < 0.0001), discriminatory (22.7%), and choice reaction time (30.5%, p < 0.05), as well as a significant reduction in memory test performance (-8.2%) post-race. Significant associations during the pre-race period were observed between discriminatory reaction time and systemic vascular resistance (r = 0.50), heart rate (r = -0.41) and cardiac output (r = 0.41), as well as memory and pulse pressure (r = -0.50), stroke volume (r = -0.44), and cardiac output (r = - 0.47). Significant changes in post-race cardiovascular function were observed in resting heart rate (31.5%), cardiac output (27.5%), mean arterial blood pressure (-5.6%), total systemic resistance (-17.6%), systolic blood pressure (-7.0%), pulse pressure (-11.2%), and rate pressure product (22.4%). There was evidence of enhanced cardiovascular function being associated with improved cognitive performance before and after the ultra-endurance event. After the race, the strongest relationship was seen between total systemic vascular resistance and choice reaction time (r = 0.41). Conclusions: Ultra endurance running is associated with marked impairments in cognitive performance that are associated (at least in part) with changes in cardiovascular function in healthy adults.